2023
DOI: 10.1021/acs.iecr.3c01447
|View full text |Cite
|
Sign up to set email alerts
|

AI Prediction of H2 Production in a Biomass Supercritical Water Gasification Fluidized Bed under Pulsating Inlets

Tianyu Wang,
Bin Wu,
Yurong He
et al.

Abstract: Supercritical water gasification (SCWG) is a promising approach with the advantages of high gasification rate, hydrogen-rich gas production, and environmental friendliness. In this work, a computational fluid dynamic-discrete element method (CFD-DEM) model is proposed to investigate and optimize the process of supercritical water (SCW) biomass gasification. The effect of pulsating SCW inlets on gasification and artificial neural network prediction of H 2 yields were conducted. The sinusoidal SCW inlet affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The results showed that a high surface area and pore volume of biochar resulted in an enhanced CO 2 capture capacity. Wang et al proposed a novel model to investigate and optimize the process of SCW biomass gasification. They studied the effects of pulsating SCW inlets on gasification and conducted artificial neural network to predict H 2 yields.…”
mentioning
confidence: 99%
“…The results showed that a high surface area and pore volume of biochar resulted in an enhanced CO 2 capture capacity. Wang et al proposed a novel model to investigate and optimize the process of SCW biomass gasification. They studied the effects of pulsating SCW inlets on gasification and conducted artificial neural network to predict H 2 yields.…”
mentioning
confidence: 99%